TANGGAP BIBIT KAKAO TERHADAP MEDIA TANAM GAMBUT DAN ULTISOL SERTA ZEOLIT - Nursanti, Ida (Jurnal Media Pertanian, 2017)
Peat soils and mineral soils have poor chemical and biological properties. The addition of mineral soil and zeolite in peat plant media will improve the soil properties. The aim of this research is to know the effect of ultisol and zeolite soil on peat media and to determine the ratio of ultisol and peat soil media and zeolite for the growth of cocoa seedlings. Implementation of research in Jambi City. The study used Completely Randomized Design (RAL) with 2 factors. Giving ultisol soil (U) with 4 levels : U0 = without ultisol soil, U1 = ultisol soil 15% by weight of planting medium, U2 = ultisol soil 20% by weight of planting medium, U3 = ultisol soil 25% weight of planting medium. Zeolite (Z) with 3 levels ie: Z0 = zeolite, Z1 = zeolite 100 g and Z2 = zeolite 200g. Observation of: height of plant (cm), dry weight of crown (g), leaf N content (%), and leaf P content (%). The observed data were analyzed using Duncan Multiple Range Test (DNMRT) and Duncan Multiple Range Test (DNMRT) test at 5% level. The administration of ultisol and zeolite soils on peat moss can significantly influence the growth of cocoa seeds, especially in plant height, dry crown weight, leaf N content and leaf P content. Ultisol soil 25% and zeolite 200g on peat media can better influence the growth of cocoa seedlings.Keywords : Peat, Ultisol, Zeolit, CocoaTanah gambut dan tanah mineral memiliki sifat kimia dan biologi kurang baik. Penambahan tanah ultisol dan zeolit dalam media tanam gambut akan dapat memperbaiki sifat tanah. Penelitian bertujuan mengetahui  pengaruh pemberian tanah ultisol dan zeolit pada media gambut serta menentukan perbandingan media tanah ultisol, zeolit dan gambut untuk  pertumbuhan bibit kakao. Pelaksanaan penelitian di Kota Jambi. Penelitian menggunakan Rancangan Acak Lengkap (RAL) dengan 2 faktor. Pemberian tanah ultisol (U) dengan 4 taraf  yaitu :U0  = tanpa pemberian tanah ultisol, U1  = tanah ultisol  15% berat medium tanam, U2=tanah ultisol 20% berat medium tanam, U3=tanah ultisol 25% berat medium tanam.  Zeolit  (Z) dengan 3 taraf yaitu :Z0= tanpa zeolit, Z1  = zeolit 100 g dan Z2 = zeolit 200g.   Pengamatan terhadap: tinggi tanaman (cm), bobot kering tajuk (g), kadar N daun (%), dan kadar P daun (%). Data hasil pengamatan dianalisa menggunakan analisis ragam dan uji Duncan New Multiple Range Test (DNMRT) pada taraf 5%. Pemberian tanah ultisol dan zeolit pada media gambut dapat mempengaruhi pertumbuhan bibit kakao secara signifikan terutama pada tinggi tanaman, bobot kering tajuk,  kadar N daun dan kadar P daun. Tanah ultisol 25% dan zeolit 200g pada media gambut dapat lebih baik mempengaruhi pertumbuhan bibit kakao.Kata kunci : Gambut,Ultisol, Zeolit, Kakao